2021
DOI: 10.4012/dmj.2020-214
|View full text |Cite
|
Sign up to set email alerts
|

The effect of sodium metasilicate on the three-dimensional chondrogenesis of mesenchymal stem cells

Abstract: As a person ages, weight-bearing cartilage tissues tend to deteriorate, leading to chronic pain that affects the sufferer's quality of life and imposes an economic burden on the healthcare system 1) . Cartilage comprises an avascular tissue, with low stem/progenitor cell populations, making it difficult to repair damage; therefore, as a suitable therapy, cell transplantation to promote cell revival in the diseased cartilage tissue has been investigated; however, a lack of source cells is a limiting factor 2) .… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 40 publications
(76 reference statements)
0
1
0
Order By: Relevance
“…In an earlier study, scaffold biodegradation in PBS promoted a silicon release as low as 2.7 µg/mL after 7 days [35]. Previously, Ren et al demonstrated that the addition of 200 ng/mL of sodium metasilicate (as a source of silica) to chondrogenic medium improved the expression of collagen II, aggrecan, the collagen type II/I ratio, the glycosaminoglycan contents, and the mechanical properties of mouse bone marrow scaffold-less 3D constructs [73]. However, while the osteogenic effects of silica have been extensively studied (increases osteoblast function, inhibits osteoclast function, promotes bone mineralisation, and induces vascular formation) [74], limited research has been conducted on the beneficial influence of silicon or silicate on chondrogenesis of stem cells.…”
Section: Discussionmentioning
confidence: 98%
“…In an earlier study, scaffold biodegradation in PBS promoted a silicon release as low as 2.7 µg/mL after 7 days [35]. Previously, Ren et al demonstrated that the addition of 200 ng/mL of sodium metasilicate (as a source of silica) to chondrogenic medium improved the expression of collagen II, aggrecan, the collagen type II/I ratio, the glycosaminoglycan contents, and the mechanical properties of mouse bone marrow scaffold-less 3D constructs [73]. However, while the osteogenic effects of silica have been extensively studied (increases osteoblast function, inhibits osteoclast function, promotes bone mineralisation, and induces vascular formation) [74], limited research has been conducted on the beneficial influence of silicon or silicate on chondrogenesis of stem cells.…”
Section: Discussionmentioning
confidence: 98%